2023
DOI: 10.1007/s00248-023-02304-9
|View full text |Cite
|
Sign up to set email alerts
|

The wild solitary bees Andrena vaga, Anthophora plumipes, Colletes cunicularius, and Osmia cornuta microbiota are host specific and dominated by endosymbionts and environmental microorganisms

Amanda Hettiarachchi,
Margo Cnockaert,
Marie Joossens
et al.

Abstract: We characterized the microbial communities of the crop, midgut, hindgut, and ovaries of the wild solitary bees Andrena vaga, Anthophora plumipes, Colletes cunicularius, and Osmia cornuta through 16S rRNA gene and ITS2 amplicon sequencing and a large-scale isolation campaign. The bacterial communities of these bees were dominated by endosymbionts of the genera Wolbachia and Spiroplasma. Bacterial and yeast genera representing the remaining predominant taxa were linked to an environmental origin. While only a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 100 publications
(140 reference statements)
0
4
0
Order By: Relevance
“…Additional isolation experiments using MRS supplemented with fructose may reveal more information on the prevalence of this organism in bumble bees. Large-scale isolation campaigns of gut samples of Asian hornets ( Vespa velutina ) and the solitary bees Andrena vaga , Anthophora plumipes , Colletes cunicularius and Osmia cornuta [13, 43] involved the use of MRS supplemented with 2 % fructose but did not yield isolates similar to strain LMG 33000 T . A Protologger analysis indicated that the same taxon was present in other insect microbiome datasets at minor relative abundances suggesting it is not a numerically abundant organism when present.…”
Section: Discussionmentioning
confidence: 99%
“…Additional isolation experiments using MRS supplemented with fructose may reveal more information on the prevalence of this organism in bumble bees. Large-scale isolation campaigns of gut samples of Asian hornets ( Vespa velutina ) and the solitary bees Andrena vaga , Anthophora plumipes , Colletes cunicularius and Osmia cornuta [13, 43] involved the use of MRS supplemented with 2 % fructose but did not yield isolates similar to strain LMG 33000 T . A Protologger analysis indicated that the same taxon was present in other insect microbiome datasets at minor relative abundances suggesting it is not a numerically abundant organism when present.…”
Section: Discussionmentioning
confidence: 99%
“…Actinobacteria are frequently isolated from soil and plants, but not often from flowers, with the exception of this study and a study on Pulmonaria nectar, in which 50% of the OTUs recovered belonged to Actinobacteria (71). Investigations of Pulmonaria pollination showed that Anthophora plumipes was an important pollinator, and separate microbial characterization of adults revealed persistent associations with Streptomyces (45). Anthophora urbana has also been found to host prevalent fungi, which are present in live brood cells (72).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the microbiome described here is complex and nearly all brood cells are dominated by 6 core bacterial genera and a single fungus. In previous work on solitary bees, brood cell bacterial microbiomes are highly variable among individuals or composed of more limited taxa (18,19,40,(44)(45)(46). Most commonly in brood cells with consistent microbial communities, lactic acid bacteria are dominant in the provisions, but disappear before pupation (18,19).…”
Section: Unique Corementioning
confidence: 99%
“…were reported as prevalent in the gut of males of the Asian tiger mosquito (Aedes albopictus: Diptera, Culicidae) and are considered to play a role in the assimilation of fructose, which is a relevant component in their nectarivorous diet [86]. As part of an extensive array of microorganisms that play a crucial role in the digestion of feed, in the absorption of nutrients and in the protection against pathogens, the occurrence of Cladosporium in the digestive tract has been documented in many unrelated insect species, both after direct isolation [3,15,19,24,26,47,50,51,58,59,78,79,100,101,118,125,127] and as a result of studies based on biochemical (e.g., denaturing gradient gel electrophoresis) and metagenomic analyses [3,40,47,88,90,101,[107][108][109]117,118,125,133,138,141,144,146,151,154,161,230]. In addition to descriptive aims, these studies have addressed various aspects that more or less influence the gut microbiome species assortment, such as age, instar, gender, caste, diet, pesticides, antibiotics and various environmental factors.…”
Section: Other Ecological Relationshipsmentioning
confidence: 99%